Zerumbone neuro-modulates spinal motor and sensory neurons of rats: a c-Fos study / Jamil Ahsan Kazi ... [et al.] - Kazi, Jamil Ahsan; Samshudin, Norsyazwani; Sabirin, Faezah; Abd Rahman, Noor Izzah (Faculty of Dentistry, Universiti Teknologi MARA, 2023)
Background: A natural sesquiterpene Zerumbone (ZER) is abundant in rhizomes of Zingiber zerumbet (L) Smith, well-known for its beneficial effects. Very few reported studies of Zerumbone (ZER) as well as its bioactive compounds focusing on its neuromodulatory activities based on it functional neuro-anatomy. Objective: The aim of this study was to investigate the neuroanatomical functional site of the zerumbone in rat spinal motor and sensory neurons by means of c-Fos immunohistochemistry. Results: Our present study demonstrated that i.p., administration of zerumbone (100 mg/kg) significantly (p<0.01) increase in the number of c-Fos immunoreactive neurons in the dorsal and ventral nuclei of the rats. Conclusion: The result of the present study strongly indicates that zerumbone has neuromodulatory effects on sensory and motor neurons. To the best of our knowledge, it is the first report which indicates that zerumbone might play crucial roles in motor and sensory neuromodulation. Our findings warrant further study to reveal the underlying molecular mechanisms of zerumbone induced sensory and motor neuromodulation. We suggest the c-Fos immunohistochemical functional mapping of zerumbone in central nervous system of model animals to reveal its therapeutics potential and mechanisms.